Contribuição ao estudo de cimentos supersulfatados: formulação e mecanismos de hidratação - Rubert, Sílvia (2015)
In recent years, considerable attention has been given to the development of special cements that can reduce CO2 emissions and energy and the consumption of limestone. Supersulfated cement are mainly composed of blast furnace slag (80- 90%), calcium sulfate (10-20%) and an alkaline activator such as Portland cement (around 5%) or alkali metal hydroxides. The supersulfated cements (SSC) were used in the years between 1950 to 1960 in Europe, especially for applications in concrete, but its lower gain strength at initial age limited their commercial application. Later changes in iron manufacturing processes generated slag which Al2O3 no longer met the requirement of minimum content required for SSC, leading to its alternative use mixtures of Portland cement (blast furnace cement). Recently, the standard for Europe supersulfated cement was replaced by EN 15743 (2010), however, the hydration mechanism and its optimum proportion are not well understood. In this study, the effects of the type and content of the alkali activator (hydroxides) and the content of slag and anhydrite were studied. The calcium and potassium hydroxide were studied in 0.2, 0.5 and 0.8% with SSC formulations containing 80 - 90% blast furnace slag and 10-20% sulfate calcium (anhydrite). Compressive strength tests showed that the content of alkaline activators influenced more than slag/anhydrite content. Mortars made with KOH with of 0.2 and 0.5% presented the highest compressive strength values; however, mortars made prepared with Ca(OH)2 presented the highest values with 0.8%. All cements prepared with 0.5% KOH as alkaline activator containing 85% of slag and 15% of anhydrite reached the EN 15743 requirements. The calorimetric measurements confirmed that the KOH provided higher heat flow rate and increased the total heat in relation to Ca(OH)2. The microstructural analysis (XRD, TG/DTG, SEM) confirmed ettringite, gypsum and C-S-H as main phases. The anhydrite should be consumed for the formation of ettringite, however when very soluble, provided a higher formation of gypsum phase.